Psalm 18 in words and pictures : a reading through metaphor - Gray, Alison Ruth. (Biblical Interpretation Series, 2013)
In Psalm 18 in Words and Pictures: A Reading Through Metaphor , Alison Gray engages in an in-depth study of the figurative language of Psalm 18, demonstrating the necessity of a dynamic approach to metaphor interpretation within a given textual unit. As one of the longest and most elaborate in the Hebrew Bible, Psalm 18 provides fertile soil for studying the interplay between words and images. While previous studies of the Psalm have focused on questions of form, structure, or unity - as well the relation to its Doppeltext of 2 Samuel 22 - Alison Gray explores the ways in which a metaphor-oriented hermeneutic enriches the psalm's translation and exegesis.